EFFORTS TO IMPROVEMENT LEARNING RESULTS THROUGH USE INTEGRATED PHYSICS LEARNING MULTIMEDIA IN THE SENIOR HIGH SCHOOL (SMA) 12 PEKANBARU - Muhammad Nasir; Budiawati Budiawati (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
This research is a classroom action research that aims to improve student learning outcomes by using integrated multimedia learning physics for senior high school or equivalent. This research was conducted at the senior high school (SMA)12 Pekanbaru. The subjects in this study were students of class X IPA 1 with 36 students consisting of 16 male students and 20 female students. The study was conducted in two cycles and consisted of 8 meetings with the details of the first cycle consisting of three meetings and three times quiz and one daily test (UH) and the second cycle consisted of four meetings consisting of three meetings and three times a and one dayly test. Each cycle is analyzed and feedback and repairs are needed. Based on the results of the study, it was found that there was an increase in individual completeness in the 1st cycle. 40.41% at quis-1, 51.65% at quis-2 and 90.81% at quis-3. Likewise, the second cycle. 80.25 in quiz-1, 85.75% in quis-2 and 90.00% in quis-3. Based on these results it was found that the increase in individual completeness in the 2nd cycle was higher and more stable. This shows that the results of individual completeness during learning both cycle-1 and cycle-2 have increased, but the increase in cycle-2 is more linear. These results indicate that learning using integrated multimedia can improve student physics learning outcomes.